Membangun Jiwa Kewirausahaan Di Era Milenial Bagi Mahasiswa Institut Stiami Kampus Tangerang Selatan - Ambarwati Ambarwati; Indra Sumarna Sobari (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2020)
In the digital world, millennial generation in Indonesia has an important role in moving the Indonesian economy forward, with the emergence of millennial entrepreneurs in the current digital era can help the problems of society such as unemployment problems in Indonesia, this is of course millennial entrepreneurship becomes an Indonesian economic power to more advanced. Technological developments in the current era of globalization provide an opportunity for millennials to be able to develop various technology-based businesses. Digital technology is becoming a necessity and a new lifestyle for the people whose utilization can be used as an opportunity to work in any field that is more productive, more creative, so that it can produce new innovations in building businesses or expanding existing ones. With the South Tangerang City Chamber of Commerce and Industry, it is hoped that there will be more opportunities for new entrepreneurs to start or expand their businesses. With various forms / types of products offered, it makes a very wide opportunity given by the South Tangerang City Chamber of Commerce and Industry to be able to work together in building a business that will be run. Products can be developed by utilizing social networks that can reach all levels of society (using market places) with good promotions and opinions, so they will get optimal results, so that reliable entrepreneurs can be created.